Structural and functional changes of bioactive proteins in donor human milk treated by vat-pasteurization, retort sterilization, ultra-high-temperature sterilization, freeze-thawing and homogenization - Liang, Ningjian; Koh, Jeewon; Kim, Bum Jin; Ozturk, Gulustan; Barile, Daniela; Dallas, David C. (Frontiers in Nutrition, 2022)
Background Donor human milk should be processed to guarantee microbiological safety prior to infant feeding, but this process can influence the structure and quantity of functional proteins. Objective The aim of this study was to determine the effect of thawing, homogenization, vat-pasteurization (Vat-PT), retort sterilization (RTR) and ultra-high-temperature (UHT) processing on the structure of bioactive proteins in donor milk. Methods Pooled donor milk was either not treated (Raw) or treated with an additional freeze-thaw cycle with and without homogenization, Vat-PT, RTR with and without homogenization, and UHT processing with and without homogenization. Overall protein retention was assessed via sodium-dodecyl sulfate (SDS-PAGE), and the immunoreactivity of 13 bioactive proteins were assessed via enzyme-linked immunosorbent assay (ELISA). Results Freeze-thawing, freeze-thawing plus homogenization and Vat-PT preserved all the immunoglobulins (sIgA/IgA, IgG, IgM) in donor milk, whereas RTR and UHT degraded almost all immunoglobulins. UHT did not alter osteopontin immunoreactivity, but Vat-PT and retort decreased it by 50 and 70%, respectively. Freeze-thawing with homogenization, Vat-PT and UHT reduced lactoferrin's immunoreactivity by 35, 65, and 84%, respectively. Lysozyme survived unaltered throughout all processing conditions. In contrast, elastase immunoreactivity was decreased by all methods except freeze-thawing. Freeze-thawing, freeze-thawing plus homogenization and Vat-PT did not alter polymeric immunoglobulin receptor (PIGR) immunoreactivity, but RTR, RTR plus homogenization and UHT increased detection. All heat processing methods increased α-lactalbumin immunoreactivity. Vat-PT preserved all the growth factors (vascular/endothelial growth factor, and transforming growth factors β1 and β2), and UHT treatments preserved the majority of these factors. Conclusion Different bioactive proteins have different sensitivity to the treatments tested. Overall, Vat-PT preserved more of the bioactive proteins compared with UHT or RTR. Therefore, human milk processors should consider the impact of processing methods on key bioactive proteins in human milk.